Efficiency of Bevel and Hypoid Gears—Test Rig Development and Experimental Investigations - Lorenz Constien; Martin Weber; Josef Pellkofer; Karsten Stahl (Machines)
The efficiency of bevel and hypoid gears is, alongside load capacity, one of their most important design criteria. To consider the efficiency of bevel and hypoid gears during the development and design process, validated calculation methods based on experimental investigations are necessary. However, the isolated experimental investigation of the load-dependent power losses of bevel and hypoid gears has not been adequately investigated, as most of the experimental investigations consider the complete gearbox. This paper presents a test rig that allows for the experimental investigation of the efficiency of bevel and hypoid gears with a measurement uncertainty of the efficiency of <semantics>∆η≤±0.08%</semantics> according to the Guide to the Expression of Uncertainty in Measurement (GUM). Using the developed test rig, experimental investigations on the efficiency behavior of bevel and hypoid gears regarding the influence of the axial offset, driving direction, and microgeometry are carried out for different operating points varying in circumferential speed and load. This paper discusses the methodology and the first experimental results of a study on the efficiency of bevel and hypoid gears in detail.